Numeracy Drama: A Creative Approach to Improving Numerical Literacy at Elementary School - Putri, Al Via Azzahra; Isnaniah, Isnaniah; Nuraini, Hery (Jurnal Basicedu, 2025)
The study of mathematics is frequently viewed as challenging and uninteresting, which has a detrimental effect on elementary school pupils' numeracy abilities. The purpose of this study is to evaluate Numeracy-Drama (N-Drama) as an innovative approach to raising fifth-grade students' numeracy proficiency. The study uses a classroom action research design and a quantitative approach with 20 students from three classes in a Tangerang Regency elementary school. With an average gain score of 9.5 and pretest scores rising from 20 to 29.5, the results show a significant improvement in average scores. By offering a fun and engaging learning environment, the N-Drama method improves students' comprehension of mathematics. Individual achievement disparities, however, point to the need for more flexible teaching strategies. Consequently, N-Drama assists students in comprehending mathematics while offering a creative learning experience, making it a potential solution to improving the quality of mathematics education in Indonesia